Families of Children with Defects in the Development of Pedagogical-Psychological Work - Nabiyev Ravshanjon Shavkatjon Ogli; Ortiqboyeva Parizoda Ismoiljon Qizi (Zien Journals, 2023)
This article with families of children with defects in the development of pedagogical-psychological works of coverage given. Disabled children mother tarbiyalayotgan pedagogical and psychological assistance causing issues mentioned
Keywords: Disabled children; family and diagnosis; ethics, chat